Integrated Analysis Using FTA, ASPEN HYSYS, And Lopa Of The 2019 HF Alkylation Unit Incident At The Philadelphia Energy Solutions Refinery - Muhammad Ridho Fauzan; Manuel Asi Saputra; M Farhan Madani; Raihan Nur Syafiq; Narisa Rayyana; Ayu Rachmawati; Eka Fitriani Ahmad (CV. AFDIFAL MAJU BERKAH, 2026)
The incident at the Hydrofluoric Acid Alkylation Unit of the Philadelphia Energy Solutions Refinery (PES) in 2019 represents a major process safety failure driven by a combination of technical and systemic weaknesses. This study analyzes the root causes, process dynamics, and adequacy of protection layers through an integrated application of Fault Tree Analysis, Aspen HYSYS process simulation, and Layer of Protection Analysis. FTA was used to identify causal relationships between basic events and the top event, while HYSYS simulation provided insight into the thermodynamic conditions of the process fluid prior to the rupture. LOPA evaluated the effectiveness of the existing protection layers. The findings indicate that the rupture of the discharge-line elbow resulted from undetected HF corrosion, improper material selection, weaknesses in the mechanical integrity program, and the absence of an emergency isolation valve. The simulation confirmed vapor-phase dominance, leading to a high-velocity jet release and rapid vapor cloud formation that subsequently ignited. LOPA revealed that most protection layers did not meet the criteria for an independent protection layer (IPL), with only the Rapid Acid Deinventory (RAD) system proving effective. These results highlight the need to strengthen protection design, implement risk-based inspection, improve material selection, and apply inherently safer design principles to prevent similar incidents in high-risk industrial facilities.